FEM Analysis of Clinching Tool Load in a Joint of Dual-Phase Steels - Kaščák, L.; Spišák, E.; Kubik, R.; Mucha, J. (Проблемы прочности, 2016)
The clinching tool with a die of 5 mm diameter with a specially formed gap and a punch of 3.6 mm diameter were used for mechanical joining of dual-phase steel sheets DP600 with the pressing force of 30 kN. The punch and die were deposited by PVD coating of CrN type with LARC technology. The coating state of each 50th manufactured join was evaluated by SEM. Cracks in the area of punch’s radius were detected. The finite element method was applied for the assessment of punch load in the joining process.